2020
DOI: 10.1016/j.jad.2020.07.135
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 pandemic on mental health & wellbeing among home-quarantined Bangladeshi students: A cross-sectional pilot study

Abstract: Highlights To the best of our knowledge, this is the first study focused on COVID-19 associated mental health among the home-quarantined Bangladeshi university and college students. University students had greater psychological impact due to COVID-19 than college students. Perceived COVID-19 symptoms were significantly associated with higher scores in DASS stress subscale (B=3.71, 95% CI: 1.01 to 6.40), DASS anxiety subscale (B= 3.95, 95% CI: 1.95 to 5.96)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

50
406
8
17

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 396 publications
(481 citation statements)
references
References 36 publications
50
406
8
17
Order By: Relevance
“…Butterworth et al reported in 2009 with the agreement of our study that food insecurity causes most serious mental health effects (Butterworth et al, 2009). Furthermore, perceiving inadequate food supply as a stressor was significantly associated with both anxiety and depressive symptoms in the present study which is consistent with a recent study which was conducted on Bangladeshi students (Khan et al, 2020). Although the multivariate analysis did not find any significant relationship of the stressor "increased price in daily commodities" with anxiety, it was found to be strongly associated with depressive symptoms even in multivariate regression.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Butterworth et al reported in 2009 with the agreement of our study that food insecurity causes most serious mental health effects (Butterworth et al, 2009). Furthermore, perceiving inadequate food supply as a stressor was significantly associated with both anxiety and depressive symptoms in the present study which is consistent with a recent study which was conducted on Bangladeshi students (Khan et al, 2020). Although the multivariate analysis did not find any significant relationship of the stressor "increased price in daily commodities" with anxiety, it was found to be strongly associated with depressive symptoms even in multivariate regression.…”
Section: Discussionsupporting
confidence: 92%
“…This could be because of the concern about the future financial crisis as 79.63% of respondents perceived the upcoming financial crisis as a stressor (Table 3). Financial uncertainty was reported as significantly associated with anxiety and depression (Khan et al, 2020). The particular interest of the current study was to explore the association between financial hardship and mental health difficulties.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Teenagers who spent more time exercising reported more positive affects, like feeling happy, valued, and confident about the future, which is not surprising given the similar results from several studies on adult populations in confinement [44] [59]. Teenagers who experienced depression symptoms were perhaps less likely to engage in physical activity because they lacked energy [58].…”
Section: Adolescents' Habits During Confinement and Internalized Sympsupporting
confidence: 62%
“…The recent COVID-19 is an ongoing global public health crisis according to WHO declaration on 30 th January, 2020 which was first emerged at Wuhan city of China [5], [6]. In Bangladesh, Institute of Epidemiology, Disease Control and Research (IEDCR) declared the first confirmed cases on 8 th March, 2020 [7]. After that country has taken numerous control measures fighting against COVID-19 though these available control measures are significantly influenced by the knowledge, attitudes, and practices (KAP) towards COVID-19 [8].…”
mentioning
confidence: 99%